Pentingnya Pendidikan Agama Islam dalam Membentuk Karakter Generasi Muda - Hidayat Hidayat (Jurnal Pendidikan Islam Indonesia, 2025)
Islamic Religious Education plays a highly strategic role in shaping the character of the younger generation to become morally upright, responsible, and possess high moral integrity. In this era of globalization, marked by rapid technological and informational advances, young people face increasingly complex challenges, including negative influences that threaten moral and spiritual values. Islamic Religious Education serves as a shield by instilling faith, piety, and noble character (akhlaq karimah) from an early age. This article aims to examine the urgency of Islamic education in character formation and to analyze effective approaches that can be applied within the family, school, and community environments. Through a qualitative method and literature review, it is found that the integration of religious knowledge, exemplary behavior, and spiritual practice can shape a holistic and competitively positive individual in society. Thus, Islamic Religious Education is a crucial foundation for producing a generation that excels not only intellectually but also morally and spiritually.